Research Into the Impact of Different Paywandtini on Fruit Quality for Intensive Gardens - Ahmadjonov Avazbek Akmaljon o'g'li (Genius Journals, 2022)
In this article, in order to study the effect of different grafts for intensive orchards on fruit quality and to study and determine the photometric indicators and biometric classification of apple trees, the following indicators are the height of the stem, the thickness of the trunk, the size of the branches The average and total length of growth of annual branches is studied, the ideas about its methods are illuminated.
Keywords: Soil; climate; combinations of intensive horticultural varieties; grafting methods